(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The electrochemical behavior of peracetic acid (PAA) in disinfectant â€œDelaksonâ€ has been studied. Materials and Methods: â€œDelaksonâ€ disinfectant is a sample preparation, which was used for the analysis. A new voltammetric method for the quantitative determination of PAA in â€œDelaksonâ€ disinfectant at the carbositall rotating electrode (CE) in the interval of potential +1.0â€¦â€“1.0 V (the reference electrode Ag, AgCl/KÐ¡l [sat]) (Ep = +0.15 V) was proposed. Results: It has been experimentally proved that height of PAA reduction peak decreases and the reduction peak potential is shifted toward more electronegative values with the background electrolyte pH increasing from 2.15 to 4.78. The optimum pH for analysis is approximately 3.6. The linear relationship has been observed in the PAA concentration range 3.12â€“12.50 Ã— 10â€“5 mol/L, the calibration curve equation was IÑ€ = (3.78 Â± 0.46) Ã— 103Ñ (r = 0.995). Determining PAA in the work solution with the relative standard deviation (RSDs) were 0.035â€“0.022 (Î´ = +0.30... +0.90%); limit of detection = 1.19 Ã— 10â€“6 mol/L, and limit of quantification = 3.97 Ã— 10â€“5 mol/L. Determining PAA in the test solution of â€œDelaksonâ€ disinfectant with the concentrations of 0.1% the RSD was 0.024 (Î´ = +0.9%). Conclusions: Thus, new voltammetric method of PAA determination in â€œDelaksonâ€ disinfectant at CE has been developed and the possibility of its quantitative determination has been shown.